Fonte fria house, Portalegre (1985-1988) - Sequeira, M. (Flashback: Carrilho da Graça, 2022)
The starting point for this project was three small rural houses built on an inland promontory in the Serra de São Mamede mountains (near Portalegre, Upper Alentejo), notable for its view over the landscape. The brief was to connect the three buildings to form a single house, but Carrilho da Graça added the re-establishment of the house’s relationship with the territory to this objective. He set out to rebuild and consolidate the existing buildings — in earth, stone and lime — placing elements that establish a mediation with the landscape — through the use of concrete, glass and water — and facing the house towards the imposing valley. The boundaries were then changed, on the one hand mitigating its relationship with the exterior by replacing part of the perimeter wall with windows, on the other hand dramatising its dominant position by advancing the outer wall to form a water tank. This work is a paradigmatic example of the importance of reading the territory in the context of Carrilho da Graça’s project process.